Public Contracts by Negotiated Procedure in Cases of Urgency – A New Interpretation of the Legal Basis in Light of Experiences with Organization of the 2012 European Football Championships - Horubski, Krzysztof (University of Wroclaw. Faculty of Law, Administration & Economics, 2013)
The negotiated procedure without publication of a contract notice is a special procedure for awarding public procurement contracts which departs from the obligation imposed on contracting authorities of respecting the freedoms of the internal market and rules of competition. The procedure may be applied in exceptional situations of extreme urgency resulting from an event which could not be foreseen. The current judicature of the Court of Justice of the EU provides interpretations of the legal basis for application of the procedure in specific cases. However, it does not address the issue of whether it is possible to regard improper performance of contractual obligations as unpredictable. It does not provide broader considerations concerning the form of regulations on the procedure of awarding public interest contracts either. These issues were subject to analysis in one of the resolutions of the National Appeal Chamber (KIO) – the Polish authority issuing decisions in matters related to public procurement contracts. In resolution KIO/KD 58/10 of 6 August 2010, KIO assessed the correctness of the application of the negotiated procedure for changing the contractor of the Municipal Stadium in Wrocław in the run-up to the 2012 European Football Championships. KIO found that the significant delay in construction of the facility was unpredictably exceptional, and significantly threatened the timeliness of commissioning the facility, which resulted in termination of the agreement by the contracting authority. The resolution also included an assessment allowing for the position that such a situation was exceptional due to the scale of the threat to the public interest, including the commercial interest of the contracting authority, stemming from a lack of immediate performance of the contract if it resulted in disproportionate consequences for a specific community. The issue of acceptance of such an interpretation by EU institutions remains unresolved.
Keywords: umowy publiczne; negocjacje; mistrzostwa Europy w piłce nożnej 2012